ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PADA MATERI KUBUS DAN BALOK UNTUK SISWA KELAS VIII SMP NEGERI 1 CILILIN - Intan Nuraeni; Fitri Nurhalisa; Nelly Fitriani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Researchers conducted research that aims to determine the problems faced by students when learning mathematics, which are the factors that cause errors in solving mathematical problems. This error factor must be known so that it is easier to get solution and the parts that need to be emphasized during learning. This research is a qualitative descriptive study to analyze and describe the types of errors made by students of class VIII SMP Negeri 1 Cililin. The written test became a data collection technique. The results of the analysis of student errors obtained: 1) 60,53% conceptual error with a “high” standar error; 2) 18,42% of program errors with a “verry low” standard of error; 3) 21% technical errors with a “very low” error rate low. This leads to the conclusion that students understanding of the cube and block material is low, and the teacher should pay attention to knowledge, emphasizing the important parts that stundents use.